Determination of Educational Success: Systems Thinking, Empowerment, Self Potential - Kholdun, Ibnu; Ali, Hapzi; Anwar Us, Kasful (Green Publisher, 2023)
This article analyzes the factors that influence the exploration of external potential and empowerment for educational success, so that the education of a student in an institution or company is able to place him/her as competent and professional human resources. The method of writing this Literature Review article is the library research method, sourced from online media such as Google Scholar, Mendeley and/or other academic online media.The results of this article are that: Determination of Educational Success 1) System Thinking, 2) Empowerment 3) Self Potential, apart from the above determination there are also other factors such as social background , culture and learning process.